Grey matter volume in adolescents with anorexia nervosa and associated eating disorder symptoms. (18th September 2017) - Martin Monzon, Beatriz; Henderson, Luke A.; Madden, Sloane; Macefield, Vaughan G.; Touyz, Stephen; Kohn, Michael R.; Clarke, Simon; Foroughi, Nasim; Hay, Phillipa
Abstract: Anorexia nervosa (AN) is a mental health disorder of complex aetiology. Previous neuroimaging studies have found consistent global reductions in global grey matter volume of underweight girls with AN; however, differences in regional grey matter volumes are less consistent. The aims of this study were to investigate grey matter regional volumes of adolescent girls with AN before and after weight recovery and the relationship of any changes with clinical characteristics. We collected high‐resolution T1‐weighted images from 26 underweight girls with AN before weight gain and 20 healthy control volunteers. Clinical features were assessed using the Eating Disorder Examination Questionnaire. AN subjects displayed reduced grey matter volumes in the insula, amygdala, prefrontal, hippocampal and cingulate cortices and the precuneus, relative to healthy controls. In a subset of 10 AN subjects who were followed after weight recovery, grey matter volumes increased to near‐control levels in the orbito‐ and medial prefrontal, insular, left hippocampal and mid‐ and posterior cingulate cortices and precuneus. The recovery of the right anterior thalamus and the left orbitofrontal cortex was correlated with improvements in eating concerns and shape concerns, respectively. However, large parts of the anterior cingulate cortex, caudate nuclei and right hippocampus did not display any grey matter recovery following a short‐term of treatment. These results show that in adolescents with AN, some brain regions display marked recovery in grey matter volume following weight recovery, whereas others do not, considering grey mater recovery possibly linked to symptom improvement. Abstract : Adolescent girls with anorexia nervosa presented decreased grey matter volumes in frontal, cingulate, insular, parietal and hippocampal cortices, the amygdala, thalamus and caudate nuclei relative to healthy controls. Short‐term weight restoration reversed these grey matter decreases in frontal, insular and posterior mid‐cingulate cortices. However, large parts of the anterior cingulate cortex, caudate nuclei and right hippocampus did not display any grey matter volume recovery.